THE ENVIRONMENTAL, SOCIAL, AND GOVERNANCE TRIAD: UNLOCKING SUSTAINABLE VALUE FOR ZAMBIA - Mwangala Simasiku; Pethias Siame (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the contemporary global landscape, governments are increasingly held accountable for their performance across the Environmental, Social, and Governance (ESG) triad. The interplay between the environment, society, and governance constitutes a complex and critical relationship that fundamentally shapes sustainable development and policymaking. These three elements interact dynamically, influencing decisions on resource management, environmental protection, public health, and economic prosperity. A nuanced understanding of this interface is imperative for formulating effective policies that advance the well-being of both society and the environment. This paper investigates the intricate dynamics of ESG factors in Zambia, highlighting the interdependencies and synergies between environmental degradation, social unrest, and governance failures. Employing a qualitative approach anchored in the Triple Bottom Line (TBL) theory, this research underscores the interconnectedness of economic, social, and environmental performance. Through an analysis of national policies and case studies, the study demonstrates that synergistic collaboration between societal actors and governmental entities is vital for fostering sustainable practices. Ultimately, recognizing and addressing these interdependencies is crucial for developing holistic strategies that promote sustainability, equity, and resilience in the face of global challenges. This study contributes to the discourse on ESG by providing insights that can inform evidence-based policies for sustainable growth in Zambia.